Tribological Behaviour of Solid Lubricants in Hydrogen Environment - Thomas Gradt (Japanese Society of Tribologists, 2011)
For further development of hydrogen technology, it is necessary to have a sufficient number of materials for safe and reliable operation available. Frictional contacts exposed to hydrogen, are critical because of vanishing protective oxide layers in the presence of a chemical reducing environment. Furthermore, liquid lubricants are often not applicable, because of purity requirements, or very low temperatures in the case of liquid hydrogen. Thus, for numerous tribosystems in hydrogen technology, solid lubrication is the only possible method for reducing friction and wear. Therefore, investigations on the tribological behaviour of friction reducing materials, such as PTFE, graphite, DLC and MoS2, in inert and hydrogen environment were carried out. The results show that solid lubricants, applied as coatings or as components in polymer composites, are able to reduce friction and wear in gaseous as well as in liquid hydrogen. However, some materials are very sensitive to the environmental medium.